Self-healing in B12P2 through Mediated Defect Recombination - Huber, S. P.; Gullikson, E.; Frye, Clint D.; Edgar, James H.; van de Kruijs, R. W. E.; Bijkerk, F.; Prendergast, D. (My University, 2016)
The icosahedral boride B12P2 has been reported to exhibit “self-healing” properties, after transmission electron microscopy recordings of sample surfaces, which were exposed to highly energetic particle beams, revealed little to no damage. In this work, employing calculations from first-principles within the density functional theory (DFT) framework, the structural characteristics of boron interstitial and vacancy defects in B12P2 are investigated. Using nudged elastic band simulations, the diffusion properties of interstitial and vacancy defects and their combination, in the form of Frenkel defect pairs, are studied. We find that boron icosahedra maintain their structural integrity even when in a degraded state in the presence of a vacancy or interstitial defect and that the diffusion activation energy for the recombination of an interstitial vacany pair can be as low as 3 meV, in line with the previously reported observation of “self-healing”.
Citation: Self-healing in B12P2 through Mediated Defect Recombination. S. P. Huber, E. Gullikson, C. D. Frye, J. H. Edgar, R. W. E. van de Kruijs, F. Bijkerk, and D. Prendergast. Chemistry of Materials 28 8415--8428 (2016) 10.1021/acs.chemmater.6b04075